MODERATING STRUCTURAL EQUATION MODELING DENGAN PARTIAL LEAST SQUARE PADA PEMODELAN PENERIMAAN DAN PENGGUNAAN DOMPET DIGITAL DI KOTA SEMARANG - Nisa, Mukrimatun; Sudarno, Sudarno; Sugito, Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2021)
Digital wallets (e-wallets) are a technology that provides a new perspective for the public on non-cash payments that are far more practical and secure in transactions. The purpose of this study is to determine the factors that influence the success or failure of implementing digital wallets (e-wallets) using the variant-based Structural Equation Modeling method (Partial Least Square). In this decade, an approach has been developed that allows the relationship between an independent variable to the dependent variable which is influenced by other latent variables called Moderating Structural Equation Modeling (MSEM), so this study uses MSEM by measuring it using the ping method. The results of the analysis show that the factors that influence acceptance defined as interest in using the technology are social influences, faciliating conditions and consumer habits. Meanwhile, the factors that influence the use of digital wallets which are defined as usage behavior are interest in use and conditions that facilitate. The use of digital wallets (e-wallets) is also indirectly influenced by social influences, conditions that facilitate and consumer habits. the factor of supporting facilities from the issuer of digital wallets (e-wallets) is a factor that affects directly and indirectly the use of digital wallets (e-wallets). Analysis of Moderating Structural Equation Modeling (MSEM) using the ping method results that experience does not affect the acceptance and use of digital wallets (e-wallets) as moderationÂ Keywords: Acceptance and Use Model, Digital Wallet (E-wallet), Partial Least Square, Moderating Structural Equation Modeling.